Science navigates new routes to sustainable agroforestry - Amézquita Collazos, Edgar (2009)
Scientists from Centro Internacional de Agricultura Tropical (CIAT) in Colombia, the FAO and others have embarked on research under the CPWF to gain a detailed understanding of the reasons why QSMAS works and to establish a plan for applying the system else where. The CPWF project responsible for the research, ‘Quesungualslash and mulch agroforestry system (QSMAS): improving crop water productivity, food security and resource quality in the sub-humid tropics,’ aims to answer six main questions: How does the system work? What are the driving factors behind its adoption? Is it sustainable? How can it be improved? What environmental services does it provide? Can the system or its components be extrapolated to other tropical areas?